Fe(Cp)2BF4: An Efficient Lewis Acid Catalyst for the Aminolysis of Epoxides - Yadav, Geeta Devi; Chauhan, ManMohan Singh; Singh, Surendra (Synthesis, 2014)
Ferrocenium tetrafluoroborate [Fe(Cp)2BF4] is an efficient Lewis acid catalyst for the aminolysis of aromatic, aliphatic, and cyclic epoxides using aniline and substituted anilines as the nucleophile to provide regioselective β-amino alcohols in 61–97% yields under solvent-free conditions at room temperature. The ring opening of cyclohexene oxide with aliphatic amines gave 2-aminocyclohexanols in 33–98% yields at 60 °C under solvent-free conditions.
Keywords: epoxides; ring opening; amino alcohols; Lewis acid; Fe(Cp)2BF4